1999
DOI: 10.1007/s002040050626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) on liver phosphoenolpyruvate carboxykinase (PEPCK) activity, glucose homeostasis and plasma amino acid concentrations in the most TCDD-susceptible and the most TCDD-resistant rat strains

Abstract: Reduced gluconeogenesis due to decreased activity of key gluconeogenic enzymes in liver, together with feed refusal, has been suggested to play an important role in 2,3,7, 8-tetrachlorodibenzo-p-dioxin (TCDD)-induced lethality in rats. This study was carried out to further analyse the toxicological significance of reduced gluconeogenesis by comparing dose-responses and time-courses of effects of TCDD on the activity of phosphoenolpyruvate carboxykinase (PEPCK) in liver, liver glycogen concentration as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 36 publications
3
38
1
2
Order By: Relevance
“…PEPCK is a key enzyme in gluconeogenesis, and studies in rodents have shown that acute toxicity of TCDD may be associated with reduced PEPCK activity, together with appetite suppression and inhibition of gluconeogenesis (Viluksela et al, 1999). We found that TCDD treatment decreased Pck1 mRNA levels in Ahr ϩ/ϩ mice but not in Ahr Ϫ/Ϫ mice (Fig.…”
Section: Tablementioning
confidence: 61%
See 1 more Smart Citation
“…PEPCK is a key enzyme in gluconeogenesis, and studies in rodents have shown that acute toxicity of TCDD may be associated with reduced PEPCK activity, together with appetite suppression and inhibition of gluconeogenesis (Viluksela et al, 1999). We found that TCDD treatment decreased Pck1 mRNA levels in Ahr ϩ/ϩ mice but not in Ahr Ϫ/Ϫ mice (Fig.…”
Section: Tablementioning
confidence: 61%
“…These observations suggest that TCDD initiates a broad cellular effort to increase protein translation by increasing ribosome assembly and decreasing amino acid catabolism, possibly through Eif3-mediated changes in protein degradation rates. In fact, increased plasma amino acid levels have been observed in TCDD-treated rats (Viluksela et al, 1999).…”
Section: Tablementioning
confidence: 98%
“…Another link between Ah receptor and PPAR functions is that both receptors influence PEPCK activity or expression [PPARs (68)(69)(70) and Ah receptor (17,71)]. Additionally, both the Ah receptor and PPARα have been connected to hyperlipidemia [Ah receptor (72) and PPAR (73)], and type 2 diabetes is associated with abnormal lipid metabolism (74).…”
Section: Reviews • Linking Dioxins To Diabetesmentioning
confidence: 99%
“…Adult-onset diabetes (13,14), whose incidence continues to rise in Western countries, is a metabolic disorder involving abnormal energy metabolism (15,16). Perhaps significantly, lethal poisoning by dioxins also involves disruption of energy metabolism, characterized by depletion of lipid stores of the affected animal (the "wasting syndrome") (17). In rats, Rozman (18) demonstrated nearly identical dose-response behavior by TCDD for suppression of food intake and inhibition of the enzyme phosphoenolpyruvate carboxykinase (PEPCK) involved in gluconeogenesis [although later work (19) with a wider range of rodents did not consistently affirm this correlation].…”
mentioning
confidence: 99%
“…As the majority of the studies pertaining to the metabolic effects of dioxin exposure use animal models mostly rodents, broad strain and species specificity demonstrates the sensitivity to wasting effect of dioxins [33,34,30,[35][36][37][38]. Many observations across such studies include impaired gluconeogenesis, decrease in body weight, and reductions in the glucose-6-phosphatase activity and gene expression of PEPCK [35,32,40,10,39].…”
Section: Resultsmentioning
confidence: 99%